The Development of CO₂ Emissions in BRICS and the Expanded BRICS+ format after the Adoption of the Paris Climate Agreement: A Comparative Analysis (2015–2024) - Király, Róbert (POLARITIES, 2026)
The article examines the development of CO₂ emissions in the countries of BRICS and the extended BRICS+ format in the period following the adoption of the Paris Climate Agreement. Using a comparative and analytical approach, the study analyses both absolute emissions and per capita emissions between 2015 and 2024, with an emphasis on identifying long-term trends and structural differences among individual states. The research applies time-series analysis to assess the dynamics of emissions before, during, and after the COVID-19 pandemic, as well as in the context of recent geopolitical developments. The findings reveal significant heterogeneity in emission trajectories, reflecting differences in economic structure, energy dependence, and political priorities. The results also highlight the limits of the Paris Agreement as a tool of global climate governance, particularly due to its voluntary nature and the absence of enforcement mechanisms. The article concludes that the effectiveness of global decarbonisation efforts will largely depend on deeper institutional coordination and stronger engagement of BRICS and BRICS+ countries.